PEMBINAAN SANITASI DAN ALAT PELINDUNG DIRI (APD) BAGI PENJAMAH MAKANAN DI KALURAHAN SINDUMARTANI, KECAMATAN NGEMPLAK, KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Sri Haryanti; Narto, Narto; Haryono, Haryono; Wittiin Khairani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Good snack food production is beneficial for small and large scale food industries to produce quality food, suitable for consumption and safe for health. This cannot be separated from the role of traders in serving buyers who are hygienic and comply with food sanitation rules.In Sindumartani District, there are still many food traders who do not implement food sanitation and use Personal Protective Equipment (PPE) for traders so that they can contaminate food and cause disease. The problem found in the field is that food traders in serving buyers pay little attention to sanitation and do not use Personal Protective Equipment (PPE). These include things that are not clean enough, not properly arranged, for example a trash bin under the table, using water to wash cutlery many times, not using an apron, not using a hair cap, not being disciplined in using a mask and not using food tongs when taking food. Efforts made to overcome this are through sanitation development and the use of Personal Protective Equipment (PPE) with education methods for food traders. Providing education on the use of PPE has increased the knowledge of MSME Food Handlers in the food sector regarding the importance of processing food hygienically